Laparoscopic En Bloc Resection of T4 Colon Cancer Invading the Spleen and Pancreatic Tail. Issue 6 (June 2016) - Chen, Tzu-Chun; Liang, Jin-Tung
Abstract : Supplemental Digital Content is available in the text.